Докажите,что [latex]sin( \frac{3 \pi }{2} + \alpha )ctg( \frac{ \pi }{2} - \alpha )+sin( \pi - \alpha )+ctg( \frac{3 \pi }{2} - \alpha )=tg \alpha [/latex]
Докажите,что
[latex]sin( \frac{3 \pi }{2} + \alpha )ctg( \frac{ \pi }{2} - \alpha )+sin( \pi - \alpha )+ctg( \frac{3 \pi }{2} - \alpha )=tg \alpha [/latex]
Ответ(ы) на вопрос:
[latex]sin( \frac{3 \pi }{2}+ \alpha )*ctg( \frac{ \pi }{2}- \alpha )+sin( \pi - \alpha )+ctg( \frac{3 \pi }{2}- \alpha )=-cos \alpha *tg \alpha + [/latex][latex]+sin \alpha +tg \alpha =-cos \alpha * \frac{sin \alpha }{cos \alpha }+sin \alpha +tg \alpha =-sin \alpha +sin \alpha +tg \alpha = [/latex][latex]=tg \alpha [/latex]
[latex]tg \alpha =tg \alpha [/latex]
Ответ: Тождество верно
P.S. Пользовалась Таблицей формул приведения
Не нашли ответ?
Похожие вопросы